China goes global : the partial power - Shambaugh, David L. (New York : Oxford University, 2013)
Here, eminent China scholar David Shambaugh delivers the book that the world has been waiting for--a sweeping account of China's growing prominence on the international stage. For three decades, analysis have been charting how the world has changed China during its era of "reform and opening"--but now it is time to understand how China is impacting the world. Drawing on five years of research and travel.
1. Understanding China's global impact -- 2. China's global identities -- 3. China's global diplomatic presence-- 4. China's and global governance -- 5. China's global economic presence -- 6. China global cultural presence -- 7. China's security presence -- 8. Coping with globalized China
Includes bibliographical references and index
Keywords: Globalization -- China